2003
DOI: 10.1128/aem.69.9.5543-5554.2003
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Transmission X-Ray, Laser Scanning, and Transmission Electron Microscopy Mapping of the Exopolymeric Matrix of Microbial Biofilms

Abstract: Confocal laser scanning microscopy (CLSM), transmission electron microscopy (TEM), and soft X-ray scanning transmission X-ray microscopy (STXM) were used to map the distribution of macromolecular subcomponents (e.g., polysaccharides, proteins, lipids, and nucleic acids) of biofilm cells and matrix. The biofilms were developed from river water supplemented with methanol, and although they comprised a complex microbial community, the biofilms were dominated by heterotrophic bacteria. TEM provided the highestreso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
271
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(285 citation statements)
references
References 41 publications
13
271
0
1
Order By: Relevance
“…These observations are in keeping with those obtained by confocal microscopies of similarly grown river biofilms (17). The area selected for detailed examination was chosen on the basis of large area survey difference maps (I709 eV-I702 eV) which quickly identify areas of high metal content.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These observations are in keeping with those obtained by confocal microscopies of similarly grown river biofilms (17). The area selected for detailed examination was chosen on the basis of large area survey difference maps (I709 eV-I702 eV) which quickly identify areas of high metal content.…”
Section: Resultssupporting
confidence: 52%
“…STXM can provide quantitative maps of chemical species at environmentally relevant concentrations (i.e., mg/kg), with a spatial resolution of better than 50 nm (15)(16)(17). Full field soft X-ray transmission microscopy has been used to examine Pseudomonas putida biofilms (18).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies of live cells using soft X-ray or electron microscopy have not been carried out to date and preliminary investigations indicate that radiation damage is a critical issue in unfixed biological samples, leading to state, and show how STXM-XAS may be used to gain more detailed spectroscopic information from hydrated biological samples than the water-window imaging technique. 66,72 Dynes et al 73 demonstrated that it is possible to perform correlative optical microscopy, TEM and STXM on a single 25 sample by using an elegant labelling technique. In this work, biofilm sections were labelled with CdSe/ZnS quantum dots designed to bind to polysaccharides.…”
Section: Hydrated Statesmentioning
confidence: 99%
“…Lawrence et al, 66 used a range of fluorescent markers to stain nucleic acids, proteins, lectins and lipids within a river biofilm sample (figure 7). Confocal laser scanning microscopy (CLSM) 35 was then used to map these components across hydrated samples contained in silicon nitride 'wet cells' 74 with spatial resolution of < 1 μm.…”
Section: Hydrated Statesmentioning
confidence: 99%
“…The other peak assignments primarily come from data presented in Myneni (2002), and they remain unconfirmed and are contradicted in some cases. For example, Lawrence et al (2003) list a lipid O-NEXAFS peak at 534 eV, which should according to Table 17.6 be due to alcohol groups. The presence of large water peaks on NOM can obscure the presence of ether moieties and can also preclude the use of combined carbon, nitrogen, and oxygen NEXAFS to measure NOM elemental ratios.…”
Section: Spectral Features and Peak Assignmentsmentioning
confidence: 99%